Exploring Female Teachers’ Intrinsic and Extrinsic Motivation to Keep Teaching the Girls in Afghanistan After the Taliban’s Ban on Girls Education - Samadi, Hangama; Rahimi, Mahmood; Rahimi, Fahim (Department of Civic Education, 2023)
Gender equality in education has long been a source of debate in Afghanistan. In general, girls face greater barriers to schooling than boys. There have been ups and downs in females' access to education over the decades, the most recent being the country's 20-year Islamic Republic rule. Afghan girls have gained greater access to school over the last two decades. However, the impetus was lost in the middle when the Taliban took control of the country and declared a blanket ban on girls' education at all levels except primary school. Some courageous Afghan women rolled up their sleeves to teach Afghan girls in secrecy. The current study is on the Afghan women's motivation for enabling educational opportunities for Afghan girls despite the ban. Through qualitative design, the study conducted interviews with these brave Afghan women facilitating educational access for Afghan girls. The data analysis applied thematic analysis through a six-stage procedure. The study found that Afghan women are using online and offline approach to reach out to Afghan girls with educational facilities. It was also found that both extrinsic and intrinsic motivation give passion and inspiration to them for teaching. Family, student enthusiasm, gender equality was some of the extrinsic motivation behind their teaching, while intrinsically they were motivated by commitment to teaching, feel of responsibility, and empowering Afghan girls. Nevertheless, they also faced barrier of lack of stable internet, and teaching and learning resources. By measuring their intrinsic and extrinsic motivation, this study intends to contribute to a better understanding of the complex factors that drive female teachers' commitment to educating girls in Afghanistan after the Taliban's prohibition.